12. DRUG COST ANALYSIS OF OUTPATIENTS AT THONG NHAT HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Building a drug formulary that aligns with the disease patterns and patient characteristics at a healthcare facility is crucial for meeting treatment needs, enhancing therapeutic effectiveness, and improving the quality of healthcare services. This study aims to analyze outpatient drug use to provide the hospital with an overview of drug utilization and guide the development of an appropriate formulary for the upcoming year.Research Subjects and Methods: A cross-sectional, retrospective study was conducted to examine the outpatient drug formulary at Thống Nhất Hospital in 2023. The study analyzed drug quantity and cost according to the drug categories defined by Circular 15/2019/TT-BYT, origin of the drugs, pharmacological classification, and ABC/VEN analysis.Results: In 2023, Thống Nhất Hospital spent over VND 214 billion on outpatient drug costs, with Western medicine accounting for 95.4% and traditional medicine 4.53% of the total cost. Originator drugs, and first and second group generics had the highest usage costs, at 34.05%, 27.45%, and 16.39%, respectively. Imported drugs accounted for 66.18% of treatment costs and 36.19% of usage volume, while domestically produced drugs accounted for 63.81% of usage volume but only 33.82% of costs. Cardiovascular drugs and endocrine system drugs were the most utilized, representing 35.95% and 17.95% of the costs, respectively. According to the ABC/VEN analysis, essential drugs (group E) were the most used, with 79.95% in quantity and 86.65% in cost. Group A drugs had a usage rate of 98.90% in quantity and 79.53% in cost. Groups B and C drugs were less frequently used in outpatient treatment at the hospital.Conclusion: The study's findings provide a scientific basis for the hospital to evaluate the drug formulary, thereby constructing a drug list for the upcoming year that aligns with disease patterns and actual treatment needs, ensuring safe, effective, and economical drug use.
Keywords: Thong Nhat Hospital; Drug Formulary; Drug Categories; ABC; VEN; Outpatient